Regulation of Infrastructure and Utilities - Asquer, Alberto. author. aut Link
IX, 222 p. 6 illus., 2 illus. in color.
Keywords: This book provides a comprehensive discussion of the public policy and management issues that are encountered in the regulation of infrastructure and utilities. Drawing from theoretical arguments and several case studies, the book is divided into three parts, namely devising regulation, installing regulation, and making regulation work. The first part covers theories of regulation, regulatory policies, strategies and tools, and regulatory reforms. The second part deals with the politics of regulation and regulatory capacity. The third part discusses regulatory commitment and investments, the performance of regulated industries, and the design of regulatory systems. Case studies pay attention to various sectors (including water, electricity, telecommunications, highways, railways, district heating, and airports) from countries in every region of the world. Alberto Asquer is Lecturer in Public Policy and Management at the School of Finance and Management of SOAS University of London, UK, where he acts as director of the Centre for Financial and Management Studies (CeFiMS) and of the Centre for Water and Development. .